PERSEPSI MASYARAKAT TERHADAP FAKULTAS SYARI’AH DAN ILMU HUKUM IAIN PADANGSIDIMPUAN - HARAHAP, SUMPER MULIA; _, AHMATNIJAR; SIREGAR, MUDZAKKIR KHOTIB (Institut Agama Islam Negeri Padangsidimpuan, 2015)
The first period of this faculty (FASIH) leaded by Dr. H. Sumper Mulia Harahap, M.Ag. with 6 departments (4 the new depertements); Ahwal Syakhsiyah, Hukum Ekonomi Syari’ah, Hukum Tata Negara (Siyasah), Perbandingan Mazhab, Ilmu Al-Qur’an dan Tafsir, serta Zakat dan Wakaf. This faculty wants to be a top faculty in the regional of Sumatera in the year of 2025 and also to gain the wants of many people to the improvement of this institute become university. Based on the available and the relevance of the efforst to develop the syari’ah field and knowlwedge of laws (syari’ah) in the region of South Tapanuli, the departments in the Fasil faculty will concentrate to both fields. This is because of two reasons; first, the presence of this faculty is the natural development to the field of laws nad the second, one serious problem is less people understand and interest in this field in the integrative and interconnective ways. This weakness can be solved by presenting of Fasih faculty in State Institute for Islamic Studies Paangsidimpuan. To this reason, this research tried to answer the general views of syari’ah knowledge and laws in South Tapanuli, and also in order to picture the hopefulness and perception of the societies to the Fasih faculty generally and specifically. This research has been done through qualitative research in the social studies and the specification about the chance and prosperity can be given as the contribution to the development of Syariah and Laws Faculty (Fasih). This research used the techniques suggested by Lexy J. Moleong by applying the theory from Bogdam, Wirk and Miller and also Lofland and Lofland. The data analyzed simultanously from collecting the data.The result of this research was that the basic problems of this field were management, lecturers or human resources, and the facilities. The management problems were the management of the institute which is done traditionally; whether it was to the private institution or even in the state institution. This made the educational institution didnot do optimally. Further, in this region there are many Islamic private schools which did not have good management in making programs about learning process. To the problems of teaching human sources (lecturers), there are still many of them still need to improve their competence to be a proffesional ones. From the perception of the societies to the Fasih, it can be concluded that in general many societies support the good planning can be implemented, and this faculty must be a top faculty to give the response to many problems of laws in the region of South Tapanuli.